2019
DOI: 10.1159/000494881
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Features that Enhance Older Adults’ Acceptance of Robots: A Mixed Methods Study

Abstract: Background: With global aging, robots are considered a promising solution for handling the shortage of aged care and companionships. However, these technologies would serve little purpose if their intended users do not accept them. While the socioemotional selectivity theory predicts that older adults would accept robots that offer emotionally meaningful relationships, selective optimization with compensation model predicts that older adults would accept robots that compensate for their functional losses. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 38 publications
(50 reference statements)
3
43
1
Order By: Relevance
“…Contrary to expectations, older people seem to accept and respond well to the use of these novel enabling technologies for remote assistance, social communication and medical care, highlighting the importance of incorporating their needs and preferences in developing effective technological solutions. In addition, when faced with a choice, they seem to prefer a service-oriented robot over the more companion-oriented robot [39]. https://doi.org/10.29328/journal.apmh.1001011…”
Section: Assisted Technology In Geriatric Care and Rehabilitation: Romentioning
confidence: 99%
“…Contrary to expectations, older people seem to accept and respond well to the use of these novel enabling technologies for remote assistance, social communication and medical care, highlighting the importance of incorporating their needs and preferences in developing effective technological solutions. In addition, when faced with a choice, they seem to prefer a service-oriented robot over the more companion-oriented robot [39]. https://doi.org/10.29328/journal.apmh.1001011…”
Section: Assisted Technology In Geriatric Care and Rehabilitation: Romentioning
confidence: 99%
“…The elderly's trust in smart elderly care mainly involves privacy security trust functional trust, service trust, and device reliability trust [51]. The concept of trust perception C4 is derived from the Integrated Technology Acceptance Model.…”
Section: Steps To Calculate Importance Based On Neighborhood Rough Setmentioning
confidence: 99%
“…Assistive robots can be further classified into two types [20]: (1) service robots like a bearlike nurse robot called Robear that can lift patients out of bed, and (2) companion robots such as Paro, a baby harp seal robot that can improve social interactions of older adults with each other and with caregivers at a care house [21]. Chu et al [22] demonstrated that older adults anticipated robots to do housework; that is, a robot comes with service functions including finding or fetching items, helping them with running errands, making meals, and so on. Similarly, Ezer et al [23] also found that older adults needed robots to help them do chores, ensure security, and provide other assistance.…”
Section: Introductionmentioning
confidence: 99%